GC-MS ANALYSIS OF THE ESSENTIAL OIL FROM THE SEED OF SWEET FENNEL (FOENICULUM VULGARE MILL. VAR. DULCE) GROWN IN TURKEY - Cosge, B.; Gurbuz, B.; Gurbuz, B.; Ipek, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Fennel (Foeniculum vulgare Miller, Apiaceae family) is an annual, biennial or perennial plant, depending on the variety, and it is native to the Mediterranean area. Fennel has been cultivated since ancient times and the leaves, stems, roots, seeds and oil are used for medical and culinary purposes. This research was carried out to evaluate the content and chemical composition of essential oil from the dried seed at the experimental fields of the Field Crops Department at the Agricultural Faculty of Ankara University, Ankara, Turkey. 10 sweet fennel lines, developed by single plant selection method in this department, and a sweet fennel population (control) grown at the experimental field of the same department were used as material. The seeds of lines and control population were sown on April 4th 2006. Seeds were sown spaced 40 cm apart and row length was 3 m. The experiment was not watered and no fertilizer was given. Harvest was made by hand on the 28th September 2006. The essential oil content was determined using an average 30 g of dried seeds and a Clevenger-type apparatus. The uncrushed seeds were distilled for 3 h in 500 ml water. The obtained essential oils were analyzed by GC-MS. The essential oil contents from the seeds of the ten sweet fennel lines ranged from 1.68 to 2.74%. The principal components in the oils of the lines were trans-anethole (92.04-95.81%) and estragole (2.59-3.80%). In seeds of the sweet fennel population 1.62% of essential oil containing 94.90% trans-anethole and 3.27% estragole were also recorded.